Application of non-invasive prenatal testing for fetal chromosomal disorders in low-risk pregnancies: a follow-up study in central China - Huang, Qiuxiang; Xu, Qiao; Chen, Meihuan; Fan, Wenli; Huang, Hailong (Frontiers in Genetics, 2025)
ObjectiveTo evaluate the performance and screening value of noninvasive prenatal testing (NIPT) in low-risk pregnancies.MethodsA retrospective analysis was conducted on 60193 low-risk pregnancies over the last 5 years. Whole-genome sequencing of maternal plasma cell-free DNA was performed using next-generation sequencing. NIPT-positive results were confirmed using amniocentesis with karyotyping and/or copy number variation sequencing and chromosomal microarray analysis. Fetal outcomes were assessed using electronic medical records or telephone calls.ResultsOverall, 598 (0.99%) NIPT-positive cases were identified. The distribution of chromosomal abnormalities included sex chromosome aneuploidies (SCAs; 55.85%), rare autosomal aneuploidies (RAAs; 20.40%), copy number variations (CNVs; 11.20%), trisomy 21 (T21; 6.86%), trisomy 13 (T13; 4.01%), and trisomy 18 (T18; 1.67%). A total of 572 (95.65%) patients with NIPT-positive results underwent amniocentesis, and 55.77% (319/572) cases were confirmed. The positive predictive values (PPV) for T21, T18, T13, SCAs, RAAs, and CNVs were 87.50%, 60.00%, 34.78%, 58.97%, 32.50%, and 69.70%, respectively, and the PPV for the trisomy was higher than that for the X-monomer in SCAs. NIPT-positive results for RAAs were common in T8, T10, T16 and T20, but T16 was the most common true positive result, accounting for 33.33% (13/39) of the cases. The termination rates of true-positive pregnancies were 100% (T21, T18 and T13), 79.49% (RAAs), 67.39% (CNVs) and 78.07% (SCAs).ConclusionThis study highlights the importance of genome-wide screening based on NIPT in low-risk pregnancies. Prenatal screening by NIPT has a high sensitivity and PPV. Moreover, it can greatly reduce invasive procedures and birth defects.